2021
DOI: 10.18196/mb.v12i2.11035
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Organizational Citizenship Behavior on the Effect of Passion and Empowerment on Job Performance

Abstract: Research aims: This research aims to analyze the mediating role of organizational citizenship behavior (OCB) on the effect of passion and empowerment on teachers' job performance.Design/Methodology/Approach: Respondents in this research were Muhammadiyah elementary school teachers in Ngampilan and Wirobrajan Districts. This research used nonprobability purposive judgment sampling with the number of respondents as many as 51 teachers. Statistical tests and data processing were then carried out utilizing the Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…Individually, the better the employee's OCB, the better his performance in helping to achieve organizational goals. This argument is similar with result of research by Amalia, et al (2021), Wicaksono &Gazali (2021), andHidayah &Harnoto (2018) that show that OCB gave a positive and significant effect to employees' performance.…”
Section: Organizational Citizenship Behavior (Ocb) Significantly Infl...supporting
confidence: 90%
See 2 more Smart Citations
“…Individually, the better the employee's OCB, the better his performance in helping to achieve organizational goals. This argument is similar with result of research by Amalia, et al (2021), Wicaksono &Gazali (2021), andHidayah &Harnoto (2018) that show that OCB gave a positive and significant effect to employees' performance.…”
Section: Organizational Citizenship Behavior (Ocb) Significantly Infl...supporting
confidence: 90%
“…Several research results concerning effects of OCB towards performance of employees prove that employees' OCB behavior significantly and positively gave effects on performance of employees. This indicates the better an employee's OCB behavior, the better his performance, because they are voluntarily willing to carry out positive activities out of their workload with the aim of helping achieve organizational targets (Hidayah & Harnoto, 2018;Amalia, et al, 2021;Wicaksono & Gazali, 2021). Thus, the researcher formulated the hypothesis as below:…”
Section: H2: Working Environment Significantly Influences Employees' ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the study also revealed that 70 percent of the participants of the study shows that the OCB explains the performance and competence towards the responsibilities of the participants on their organization. This also supported the study of Yao & Mingchuan (2010) and Amalia et al (2021) were the organizational citizenship behavior explained 65 percent of individual competence in performing the job, thus, OCB had a positive effect on school heads performance which explain that the organizational citizenship behavior of individual, group and organizational competence in performing such job roles in an organization are positively related (Soumendu & Arup, 2007;Boerner et al (2007); Chiang (2012); Luthans (2011). Added on, the role of adversity quotient is interrelated on the ability or competence and achievement of a person which is 66.67 percent (Suryadi & Santoso, 2017), while with knowledge and understanding is 27.78 percent and with positive attitude is 5.56 percent, based on systematic review and meta-analysis (Juwita, 2020).…”
Section: Introductionsupporting
confidence: 77%
“…HR managers are able to encourage the creation of a positive work environment to increase job resources. There are several recommendations during pandemic conditions and work changes, namely: work facilities that have been provided, such as digital work platforms and infrastructure need to be balanced with the ability to use them; encouraging the ability and achievement of employees to strengthen engagement, accordance with research conducted by Amalia, Wahyuningsih & Surwanti (2021) that increased capability and flexibility can enhance employee achievement and engagement; creating channels for the availability of good information and communication; supporting from the superiors regarding the improvement of the competence and the needs of employees (Sulistiyani, 2022), feedback, clarity of roles both within the team and in the organization; autonomy and flexibility in work and empowerment. Another alternative approach that can be taken to reduce the effects of changes occurring at COVID-19 pandemic is to strengthen work specialization.…”
Section: Discussionmentioning
confidence: 99%